A REVIEW ON POTENTIAL USES OF CULINARY VEGETABLES USED IN ROUTINE LIFE AS AN ANTICANCER AGENT - B, Lavanya; V, Jayashree; S, Jeevaraj (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Cancer is a disease which leads to death, and chemotherapy is a treatment used to treat cancer. Lung cancer and breast cancer are most effective one in the world. The present study examines the anticancer property of culinary vegetables such as Allium vegetables, cruciferous vegetables, and beetroot which are used in day-to-day life have anticancer properties. Allicin and gallic acid in garlic decreases the risk of colon, pancreas, stomach, esophagus, and breast cancers. In onion, cysteine sulfoxide is sulfur compounds which have ant-cancer, antiplatelet, and antithrombotic property. In broccoli, glucosinolates and sulfur compounds play a major role in the treatment of breast and prostate cancer. Betacyanin is a compound present in beetroot which has antioxidant property and anticancer activity.